Exploring the Role of Gut Microbiota in the Pathogenesis of Inflammatory Bowel Disease: Insights from Metagenomic Analysis - Haris, Fadlan (Magenta Journal De Healthymedi, 2024)
Inflammatory bowel diseases (IBD), encompassing Crohn's disease (CD) and ulcerative colitis (UC), are chronic gastrointestinal disorders characterized by inflammation of the digestive tract. The gut microbiota plays a crucial role in IBD pathogenesis, yet its specific taxonomic and functional alterations remain to be fully elucidated. In this study, we conducted metagenomic sequencing analysis to investigate the composition and functionality of the gut microbiota in patients with CD or UC compared to healthy controls. Stool samples were collected from a cohort of patients with CD or UC and healthy controls, and metagenomic sequencing was performed using a state-of-the-art sequencing platform. Bioinformatics analysis revealed distinct taxonomic profiles and functional pathways in CD/UC patients compared to healthy controls. Our findings provide valuable insights into the microbial dysbiosis associated with IBD and highlight potential targets for therapeutic interventions aimed at restoring microbial homeostasis. This study contributes to advancing our understanding of the complex interplay between the gut microbiota and IBD pathophysiology, paving the way for personalized approaches to IBD management.